APPLICATION OF HEALING ARCHITECTURE IN THE INTERIOR OF A CANCER FIGHTER SHELTER HOUSE - Cut Devi Intan Sukma; Didit Widiatmoko Suwardikun; Hanif Azhar; Yanuar Rahman; Santi Salayanti (Adisam Publisher, 2025)
The increasing number of cancer patients in Indonesia encourages the need for adequate supporting facilities, especially for patients outside the region who undergo treatment in Bandung and need a temporary place during the healing process. Yayasan Rumah Cinta Insani in Bandung is one of the halfway houses that accommodates cancer patients, especially children to adolescents and their families. However, the inadequate layout, facilities, comfort, and accessibility make this environment unable to fully support the healing process. Applying the Healing Architecture concept to the interior of the halfway house is a key solution to create an environment that is healthier, safer, and supports the physical and mental well-being of patients. Key design elements include natural lighting, ventilation, color, comfort, and accessibility. This research uses a qualitative method with a Design Thinking approach, including five stages: empathize through observation and interviews with patients, caregivers, and managers; define the main problem to find a solution; ideate presents ideas; prototype as the result; and test to evaluate the proposed design. The goal is to produce a more humane, flexible, and efficient halfway house. The expected result is an environment that supports holistic healing, improves comfort for patients and families, and adapts to resident needs